Hubungan Personal Hygiene, Kecemsan, Peran Petugas Kesehatan Terhadap Kejadian Keputihan pada Wanita Usia Subur (WUS) di Kampung Panahegan RT.02 RW.02 Desa Gasol Cianjur Tahun 2023 - Dewi, Ayyu Thriesna; Fatimah, Jesy; Rini, Ageng Septa (Indonesian Journal Publisher, 2023)
Vaginal discharge is a common female reproductive health problem. Vaginal discharge can be caused by various factors, one of which is poor personal hygiene. The aim of this research is to determine the relationship between personal hygiene, anxiety and the role of health workers on the incidence of vaginal discharge in women of childbearing age. This research method uses a quantitative research design with a cross sectional approach with a population of 40 women of childbearing age in KP. Panahegan, Gasol Village, Cianjur. The researcher took a sample of 40 people. The results of research using the Chi-square test show that there is a significant relationship between personal hygiene and the incidence of vaginal discharge (P value = 0.019). The better the personal hygiene, the lower the incidence of vaginal discharge. There is a relationship between anxiety and the incidence of vaginal discharge (P value = 0.009). There is a significant relationship between the role of health workers and the incidence of vaginal discharge (P value = 0.026). The better the respondent's perception of the role of health workers, the lower the incidence of vaginal discharge.